Analisa Performansi Jaringan 5G pada Kondisi Line-of-Sight Menggunakan Frekuensi 3.3 GHz di Sawahan, Surabaya - Solichah Larasati Larasati; Khoirun Ni'amah; Zein Hanni Pradana (Journal of Information Technology and Its Utilization, 2022)
This research is expected to be the beginning of the initial design for the implementation of 5G technology in Indonesia especially in Area Sawahan, Surabaya based on the coverage area with the frequency of 3.3 GHz. Performance analysis with line-of-sight (LOS) conditions using propagation model urban macro (uMa) according to the recommendation of 3GPP (3rd Generation Partnership Project) TR 38.901. This research based on four scenarios, outdoor-to-outdoor (O2O) for downlink and uplink, and outdoor-to-indoor (O2I) scenario for uplink and downlink. Performance of 5G network simulated using Atoll 3.4 and shown the pathloss values ​​of 105.405 dB for uplink and 101.405 dB for downlink. The performance results in the O2O scenario for the uplink direction require 5 gNodeB and 8 gNodeB in the downlink direction. In the O2I scenario, the uplink direction requires as many as 6 gNodeB and the downlink direction as much as 9 gNodeB. The simulation parameters analyzed in this research are based on the signal strength received by the user (SS-RSRP) and signal quality (SS-SINR). The best result of SS-RSRP in the O2I uplink scenario is -89 dBm and the SS-SINR parameter in the O2O scenario is 0.93 dBm. These results show that in the city of Sawahan a 5G system can be applied.